2013
DOI: 10.18061/emr.v9i1.3729
|View full text |Cite
|
Sign up to set email alerts
|

Music and Lyrics Interactions and their Influence on Recognition of Sung Words: An Investigation of Word Frequency, Rhyme, Metric Stress, Vocal Timbre, Melisma, and Repetition Priming

Abstract: This study investigated several factors presumed to influence the intelligibility of song lyrics. Twenty-seven participants listened to recordings of musical passages sung in English; each passage consisted of a brief musical phrase sung by a solo voice. Six vocalists produced the corpus of sung phrases. Eight hypotheses derived from common phonological and prosodic principles were tested. Intelligibility of lyrics was degraded: (i) when archaic language was used; (ii) when words were set in melismatic rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
(27 reference statements)
0
24
0
2
Order By: Relevance
“…While Johnson et al (2014) observe in their conclusion that only half their predictions were upheld, and three findings were statistically significantly in the wrong direction, as it were, there is in my view no need to be apologetic about this. As they say, it was an exploratory study, and for this reason they justify establishing an alpha level of 0.1 for their statistical tests.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…While Johnson et al (2014) observe in their conclusion that only half their predictions were upheld, and three findings were statistically significantly in the wrong direction, as it were, there is in my view no need to be apologetic about this. As they say, it was an exploratory study, and for this reason they justify establishing an alpha level of 0.1 for their statistical tests.…”
Section: Resultsmentioning
confidence: 71%
“…THE study reported by Johnson, et al (2014) is a follow-up to Collister and Huron's (2008) investigation of the intelligibility of sung text in English. To summarize the background to that study, Smith and Scott (1980) and Benolken and Swanson (1990) reported that listeners find it hard to distinguish between different vowels when sung at high pitch by a trained soprano.…”
Section: Abstract: Singing Words Recognition Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that native speakers of (probably standard American) English find stress-matched text settings more intelligible than stress-mismatched text settings (Gordon, Magne, & Large, 2011;Johnson, Huron, & Collister, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also true that there are spontaneous spoken utterances that can sound as if they were sung. At first glance it seems difficult to unravel the phenomena that are common in both song and speech, but a reasonable number of scholars have already compared speech and music regarding memory, melody perception, intelligibility, rhythm and intonation [1,2,3,4,5,6]. Although these studies reveal differences between musical and speech elements, they shed light on the interplay between pitch and rhythm.…”
Section: Introductionmentioning
confidence: 99%